Adverse Childhood Experiences and the Consequences on Neurobiological, Psychosocial, and Somatic Conditions Across the Lifespan - Herzog, Julia I.; Schmahl, Christian (Frontiers in Psychiatry, 2018)
Introduction: Adverse childhood experiences (ACE) such as sexual and physical abuse or neglect are frequent in childhood and constitute a massive stressor with long-lasting adverse effects on the brain, mental and physical health. The aim of this qualitative review is to present a concise overview of the present literature on the impact of ACE on neurobiology, mental and somatic health in later adulthood. Methods: The authors reviewed the existing literature on the impact of ACE on neurobiology, mental and somatic health in later adulthood and summarized the results for a concise qualitative overview. Results: In adulthood, the history of ACE can result in complex clinical profiles with several co-occurring mental and somatic disorders such as posttraumatic stress disorder, depression, borderline personality disorder, obesity and diabetes. Although a general stress effect in the development of the disorders and neural alterations can be assumed, the role of type and timing of ACE is of particular interest in terms of prevention and treatment of ACE-related mental and somatic conditions. It has been suggested that during certain vulnerable developmental phases the risk for subsequent ACE-related disorders is increased. Moreover, emerging evidence points to sensitive periods and specificity of ACE-subtypes in the development of neurobiological alterations, e.g., volumetric and functional changes in the amygdala and hippocampus. Conclusion: Longitudinal studies are needed to investigate complex ACE-related characteristics and mechanisms relevant for mental and somatic disorders by integrating state of the art knowledge and methods. By identifying and validating psychosocial and somatic risk factors and diagnostic markers one might improve the development of innovative somatic and psychological treatment options for individuals suffering from ACE-related disorders.